Community as a Medium for Promoting Cultural Tourism (Study on Ternate Heritage Society Community) - Hardi, Syientani Salwa; Fahri, Johan (AIBPM Publisher, 2023)
A community is a forum where individuals gather to form a group that takes the initiative to start a process of activities that can improve the situation and condition oneself to carry out positive actions to solve community welfare problems. In addition, the community plays an active role as a forum for distributing various information and promoting tourist attractions. This study explores tourism promotion through a community, especially cultural tourism in Ternate City, North Maluku, Indonesia. This community is called the Ternate heritage Society Community (THS). This study used an ethnographic qualitative approach, and data collection was obtained through observation, interviews, and documentation. This study was conducted in Ternate City using Charmaz's approach. The results of this study show that THS has used a community branding strategy as a form of cultural tourism promotion in Ternate City. Based on the findings, the community covers two aspects—Branding and medium of Promotion. In terms of branding, it can be defined that branding of a cultural community refers to cultural identity, agent of change, and internalized cultural values. Six indicators formed this definition—existing role models, establishing community categories, being motivated, timelines, and character uniqueness of the community. Regarding the medium of Promotion, THS has been an agent of Promotion by optimizing digital marketing for millennials. Future studies are also suggested on promoting cultural heritage to the youth.